The paradox of Svalbard : climate change and globalisation in the Arctic - Sokolíčková, Zdenka, 1983- (Anthropology, culture, and society., 2023)
"The town of Longyearbyen in the high Arctic is the world's northernmost settlement. Here, climate change is happening fast. It is clearly seen and sensed by the locals; with higher temperatures, more rain and permafrost thaw. At the same time, the town is shifting from state-controlled coal production to tourism, research and development, rapidly globalising, with numerous languages spoken, cruise ships sounding the horn in the harbour and planes landing and taking off. Zdenka Sokolickova lived here between 2019 and 2021, and her research in the community uncovered a story about the conflict between sustainability and the driving forces of politics and economy in the rich global North. A small town of 2,400 inhabitants at 78 degrees latitude north on the Norwegian archipelago of Svalbard, Longyearbyen provided a unique view into the unmistakable relationship between global capitalism and climate change"--